2021
DOI: 10.1038/s41598-021-84753-1
|View full text |Cite
|
Sign up to set email alerts
|

Low nitrogen retention in a Japanese cedar plantation in a suburban area, western Japan

Abstract: This study aimed to evaluate nitrogen (N) leaching from Japanese cedar, the main plantation species in Japan, in response to elevated atmospheric N deposition. N leaching and possible factors, including soil nitrification, tree N uptake, and topographic steepness, were evaluated in mature (64–69 year) Japanese cedar trees planted on steep slopes (25°–40°) and neighboring Japanese oak plantations in suburban forests, which served as reference sites. N fertilization (50 kg N ha−1 year−1 as ammonium nitrate) was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…In IJR and KJK, the thinning of trees and declining atmospheric N deposition appear to have synergistically contributed to suppressing N leaching for several years, although this effect disappeared after a few years in the latter catchment. The high percentage of Japanese cedar in KJK (see Table 1) appears to have also contributed to high N leaching, as suggested by other studies (Nishina et al 2017;Watanabe et al 2018;Yang and Chiwa 2021). The factors mentioned above may affect utilization efficiency of Nr species derived from the atmospheric deposition in plant-soil systems.…”
Section: Changes In Stream Water Chemistrymentioning
confidence: 65%
“…In IJR and KJK, the thinning of trees and declining atmospheric N deposition appear to have synergistically contributed to suppressing N leaching for several years, although this effect disappeared after a few years in the latter catchment. The high percentage of Japanese cedar in KJK (see Table 1) appears to have also contributed to high N leaching, as suggested by other studies (Nishina et al 2017;Watanabe et al 2018;Yang and Chiwa 2021). The factors mentioned above may affect utilization efficiency of Nr species derived from the atmospheric deposition in plant-soil systems.…”
Section: Changes In Stream Water Chemistrymentioning
confidence: 65%
“…Fukushima et al (2011) evaluated N uptake rates of Japanese cedars at different ages (5-89 years old) and demonstrated that the N uptake rates of Japanese cedars were higher in younger stands (53 kg N ha −1 yr −1 in 16 years old) than in older stands (29 kg N ha −1 yr −1 in 31 years old; 24 kg N ha −1 yr −1 in 42 years old; 34 kg N ha −1 yr −1 in 89 years old). In addition, Yang and Chiwa (2021) found that the nitrate concentration in the soil water taken beneath the rooting zone of matured artificial Japanese cedar plantations (607 ± 59 µM; 64-69 years old) was significantly higher than that of normal Japanese oak plantations (8.7 ± 8.1 µM; 24 years old). Moreover, by adding ammonium nitrate (50 kg N ha −1 yr −1 ) to the forest floor directly, Yang and Chiwa (2021) found that the nitrate concentration in the soil water of the matured artificial Japanese cedar plantations increased significantly faster than that of the normal Japanese oak plantations, probably because of the lower N uptake rates in the matured artificial Japanese cedar plantations.…”
Section: Excess Leaching Of Unprocessed Atmospheric Nitrate From Fk C...mentioning
confidence: 97%
“…Moreover, by adding ammonium nitrate (50 kg N ha −1 yr −1 ) to the forest floor directly, Yang and Chiwa (2021) found that the nitrate concentration in the soil water of the matured artificial Japanese cedar plantations increased significantly faster than that of the normal Japanese oak plantations, probably because of the lower N uptake rates in the matured artificial Japanese cedar plantations. Because most of the artificial Japanese cedar/cypress plantations in the FK and MY catchments have reached their maturity (> 50 years; Yang and Chiwa, 2021), the higher proportion of matured artificial Japanese cedar/cypress plantations in the FK1 catchment (Table 1) was highly responsible for the observed elevated leaching of nitrate, caused by the reduction in N uptake rates.…”
Section: Excess Leaching Of Unprocessed Atmospheric Nitrate From Fk C...mentioning
confidence: 99%
“…In general, four nitrate removal have been identified including surface runoff, groundwater, plant uptake and microbial degradation in soil. While a large number of studies have looked into the nitrate runoff loss, plant uptake and microbial degradation in soil (Dong et al, 2020; Li, Li, et al, 2018; Yang & Chiwa, 2021; Zhu et al, 2012), less is investigated on nitrate retention in hyporheic zone ‐ the interface between groundwater and surface water, which plays an active and important role in biogeochemical processes (Kroeger & Charette, 2008; Danielescu & Mac Quarrie, 2011; Danielescu & Mac Quarrie, 2013; Gleeson et al, 2013; Binley et al, 2013; Boano et al, 2014; Wang et al, 2015; Li, Barreto, et al, 2018; Hare et al, 2021). In a study on surface water‐groundwater‐exchange, Saunders and Kalff (2001) compared the magnitude of nitrate retention in wetlands, lakes and rivers, and they found that wetlands retained the highest proportion of total nitrate loading.…”
Section: Introductionmentioning
confidence: 99%